The economics of international monies - Jr. Gerald P. Dwyer; James R. Lothian (Federal Reserve Bank of Atlanta, 2003)
The economics of international monies is likely to be informative about the future of the euro. The authors summarize the history of international monies, from the gold solidus introduced in the fourth century to the present. They identify four common characteristics of these currencies: high unitary value; relatively low inflation rates; issuance by major economic and trading powers; and spontaneous, as opposed to planned, adoption. Recent theoretical literature supports the importance of the characteristics, while recent theories' common implication of multiple equilibria supports the importance of spontaneous adoption as developed by Menger and Hayek.
Keywords: 330